Seni â€œSarafal Anamâ€ di Bengkulu: Makna, Fungsi dan Pelestarian - Muhammad Tarobin (Jurnal Bimas Islam, 2015)
Abstract This article describes about the art of Sarafal anam in Bengkulu. This is important because the value of the history of the art. Transcription of the poem of Sarafal anam displayed in Bengkulu community tradition proves that the text of the Sarafal anam different from Sharf al-anam text is in Arabic tradition. Meanwhile, some of the poems indicating closeness between Syiâ€™ah and Sunni Islamic tradition. This article also describes three Sarafal anam meaning of art in Bengkulu society such as: togetherness, beauty, religiousity. The meaning of togetherness with tradition is still upheld in customary of Bengkulu, that is bimbang tradition. While the beauty of this art looks in appearance of the accompaniment of musical instruments like drum when it reached to the stage of a blow "rentak kudo". As well as the religious value of this art representing Malay Islamic art. Abstraksi Tulisan ini mengkaji seni Sarafal anam di Bengkulu. Hal ini penting karena nilai sejarah dari kesenian ini. Transkripsi terhadap syair Sarafal anam yang ditampilkan dalam tradisi masyarakat Bengkulu ini membuktikan bahwa teks Sarafal anam tersebut berbeda dengan teks Sharf al-anam yang ada dalam tradisi Arab. Sementara itu, beberapa syair jawabnya mengindikasikan kedekatan antara tradisi Islam Syiâ€™ah dan Sunni. Artikel ini juga menjelaskan tentang tiga makna seni Sarafal anam dalam masyarakat Bengkulu yakni: kebersamaan, keindahan, religiusitas. Makna kebersamaan sejalan dengan tradisi yang masih dijunjung tinggi dalam adat Bengkulu, yakni tradisi bimbang. Sedangkan keindahan tampak dalam penampilan kesenian ini dengan iringan alat musik gendang ketika mencapai tahap pukulan â€œrentak kudoâ€. Demikian juga nilai religius dari kesenian ini menggambarkan kesenian Melayu yang Islami.